2014
DOI: 10.1111/joop.12072
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness as a cognitiveemotional segmentation strategy: An intervention promoting worklife balance

Abstract: Employees struggling with work‐related cognitions, emotions, and associated energy levels during non‐work time can find their private roles impaired and work–life balance derogated. To reduce unwanted psychological preoccupation with work concerns, boundary theory suggests employees find their ideal way to integrate or segment both life domains. In this study, the authors design and evaluate an intervention teaching mindfulness as a cognitive–emotional segmentation strategy to promote work–life balance. They u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
172
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(207 citation statements)
references
References 117 publications
(178 reference statements)
5
172
0
3
Order By: Relevance
“…It has also been shown to confer benefits on various wellbeing 3 related outcomes; for example, coping capabilities, purposefulness in life and the experience of positive emotions (e.g., Fredrickson et al, 2008). With regard to occupational health, mindfulness has been shown to be effective in: reducing daily hassles, psychological distress, and medical symptoms (Williams, Kolar, Reger, & Pearson, 2001;Dane, 2011); reducing emotional exhaustion and improving job satisfaction (Hulsheger et al, 2013); increasing employee engagement (Leroy, Anseel, Dimitrova, & Sels, 2013); improving sleep quality (Wolever, Bobinet, McCabe, Mackenzie, Fekete, Kusnick, et al, 2012;Hulsheger, Lang, Depenbrock, Fehrmann, Zijlstra, & Alberts, 2014;Hulsheger, Feinholdt, & Nubold, 2015); reducing perceived stress (Wolever et al, 2012); and increasing psychological detachment from work and satisfaction with work-life balance (Michel, Bosch, & Rexroth, 2014).…”
Section: Mindfulnessmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown to confer benefits on various wellbeing 3 related outcomes; for example, coping capabilities, purposefulness in life and the experience of positive emotions (e.g., Fredrickson et al, 2008). With regard to occupational health, mindfulness has been shown to be effective in: reducing daily hassles, psychological distress, and medical symptoms (Williams, Kolar, Reger, & Pearson, 2001;Dane, 2011); reducing emotional exhaustion and improving job satisfaction (Hulsheger et al, 2013); increasing employee engagement (Leroy, Anseel, Dimitrova, & Sels, 2013); improving sleep quality (Wolever, Bobinet, McCabe, Mackenzie, Fekete, Kusnick, et al, 2012;Hulsheger, Lang, Depenbrock, Fehrmann, Zijlstra, & Alberts, 2014;Hulsheger, Feinholdt, & Nubold, 2015); reducing perceived stress (Wolever et al, 2012); and increasing psychological detachment from work and satisfaction with work-life balance (Michel, Bosch, & Rexroth, 2014).…”
Section: Mindfulnessmentioning
confidence: 99%
“…In a recent study , Michel et al (2014) suggested that mindfulness could prove to be an effective remedy for rumination because it would provide an effective cognitive-emotional segmentation strategy to help shape boundaries between work and home lives. Furthermore, learning mindfulness may enable people to accept (without judgement) their thoughts and feelings.…”
Section: Mindfulness To Aid Recovery From Workmentioning
confidence: 99%
“…En el mismo sentido, Michel, Bosch & Rexroth (2014) manifiestan que los individuos que incorporan prác-ticas de atención plena (mindfulness) mejoran su distanciamiento psicológico del trabajo cuando están fuera del ámbito laboral, experimentando menos conflicto basado en tensión o agotamiento y aumentando la satisfacción con su equilibrio trabajo-vida.…”
Section: Tipos De Estrategias Individualesunclassified
“…Future research should consider additional measures of correctional officer mental and physical health. The growing literature on mindfulness could be particularly instructive in programs and training that could be developed to reduce employee complacency and in turn increase officer and organizational safety (Michel, Bosch, & Rexroth, 2014). Measures of physical health may lead to organizational modifications that reduce use of sick time and rates of employee absenteeism (Magnavita & Garbarino, 2013).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%